2013
DOI: 10.1016/j.devcel.2013.02.014
|View full text |Cite
|
Sign up to set email alerts
|

A Sequence in the Drosophila H3-H4 Promoter Triggers Histone Locus Body Assembly and Biosynthesis of Replication-Coupled Histone mRNAs

Abstract: Compartmentalization of RNA biosynthetic factors into nuclear bodies (NBs) is a ubiquitous feature of eukaryotic cells. How NBs initially assemble and ultimately affect gene expression remains unresolved. The histone locus body (HLB) contains factors necessary for replication-coupled histone mRNA transcription and processing and associates with histone gene clusters. Using a transgenic assay for ectopic Drosophila HLB assembly, we show that a sequence located between, and transcription from, the divergently tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
147
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(167 citation statements)
references
References 61 publications
19
147
1
Order By: Relevance
“…72,73 In addition, the sequence in histone pre-mRNA that binds U7 snRNP is not required for U7 snRNP recruitment to the Drosophila HLB. 74 Instead, we found that the C terminus of FLASH, likely together with Mxc, is necessary for recruitment of U7 snRNP to the HLB. 72 Thus, there are interactions among HLB components involved in assembling the HLB that are distinct from the interactions required for histone mRNA biosynthesis.…”
Section: Self-organization Of the Hlbmentioning
confidence: 63%
See 2 more Smart Citations
“…72,73 In addition, the sequence in histone pre-mRNA that binds U7 snRNP is not required for U7 snRNP recruitment to the Drosophila HLB. 74 Instead, we found that the C terminus of FLASH, likely together with Mxc, is necessary for recruitment of U7 snRNP to the HLB. 72 Thus, there are interactions among HLB components involved in assembling the HLB that are distinct from the interactions required for histone mRNA biosynthesis.…”
Section: Self-organization Of the Hlbmentioning
confidence: 63%
“…Indeed, we discovered a specific sequence in the Drosophila RD histone gene array that is necessary and sufficient to nucleate HLB assembly. 74 The Drosophila RD histone locus is composed of »100 copies of a tandemly arrayed 5kb sequence containing one copy of H1 and one copy of divergently transcribed H3/H4 and H2A/H2B gene pairs 1 (Fig. 3).…”
Section: Self-organization Of the Hlbmentioning
confidence: 99%
See 1 more Smart Citation
“…How HLBs (and other nuclear bodies) are formed remains a matter of debate, and models, including both highly hierarchical and random events, have been proposed (29,(37)(38)(39)(40)(41). In Drosophila, the initial step in HLB formation involves the recognition of chromatin at a specific site in the histone gene loci by a yet unidentified mechanism and subsequent recruitment of multi sex combs (Mxc), the Drosophila orthologue of NPAT, and FLASH, followed by the recruitment of the U7 snRNP and other pre-mRNA processing factors (42). At least some of these factors are recruited to HLBs prior to expressing histone genes, i.e.…”
mentioning
confidence: 99%
“…At least some of these factors are recruited to HLBs prior to expressing histone genes, i.e. in a manner independent of the presence of the histone pre-mRNAs (27,29,(42)(43)(44), indicating that the initial phase of HLB assembly is primarily driven by protein-protein interactions. Protein-RNA interactions that emerge following the initiation of transcription on histone genes likely contribute to formation of the fully developed and readily detectable HLBs (45).…”
mentioning
confidence: 99%